Harmonizing HRM: the art of strategic record keeping - Chik, Nor Kamariah; Saad, Abidah (Universiti Teknologi MARA, Kedah, 2024)
Record keeping is the methodical and structured procedure of generating, upholding, retaining, and administering records. These records encompass papers, data, or information that an entity or individual must retain for diverse objectives, including legal, regulatory, historical, or operational purposes. The maintenance of accurate and comprehensive records is of utmost importance in several domains of both professional and personal spheres. Record keeping is not solely a mundane administrative duty, but rather a skill that demands deliberate preparation and implementation. The resource indicates that it will delve into the artistic and contemplative elements of record keeping, emphasising its significance in attaining organisational objectives.